Zeolitic Imidazolate Framework-Derived Core-Shell-Structured CoS2/CoS2-N-C Supported on Electrochemically Exfoliated Graphene Foil for Efficient Oxygen Evolution - Cao, Junhui; Lei, Chaojun; Yang, Bin; Li, Zhongjian; Lei, Lecheng; Hou, Yang; Feng, Xinliang (Batteries & Supercaps, 2019)
Developing earth-abundant transition-metal based materials to efficiently catalyze the oxygen evolution reaction (OER) is an urgent demand for electrochemical water splitting and rechargeable metal-air batteries. Here, we developed a novel 3D hybrid electrocatalyst consisting of core-shell structured CoS2/CoS2 embedded into N-doped carbon supported on electrochemically exfoliated graphene foil (EG/CoS2/CoS2-NC) by sulfurization treatment of EG/Co(OH)2/zeolitic imidazolate framework-67 (ZIF-67) as precursor. The thickness of the CoS2-NC shell derived from ZIF-67 is 10 nm and the CoS2 core generated from Co(OH)2 nanosheet arrays has a particle size of ∼20 nm. Benefiting from the unique 3D core-shell structure and synergistic effects, the EG/CoS2/CoS2-NC hybrid enormously promotes electrocatalytic OER activity with a low overpotential of 210 mV at a current density of 10 mA cm−2 and a small Tafel slope of 61.9 mV dec−1. These values are far superior compared to the commercial Ir/C catalyst, and even better than other reported state-of-the-art CoS2-based materials. In-situ Raman spectroscopy together with ex-situ XRD patterns reveal that the active centers of EG/CoS2/CoS2-NC hybrid are proven to be Co-OOH species that are derived from Co−S groups during the OER process. The superb catalytic performance is also reflected in boosting electrochemical urea oxidation and hydrazine oxidation, where the accelerated oxidation reaction could be observed.
CRIS-Team Scopus Importer:2023-03-20
Keywords: active sites; cobalt dichalcogenides; core-shell structures; nitrogen-doped carbon; oxygen evolution reaction